Regulating Labour in the Wake of Globalisation: New Challenges, New Institutions - Gould, Anthony M. (Relations industrielles / Industrial Relations, 2008)
Regulating Labour in the Wake of Globalisation: New Challenges, New Institutions, edited by Brian Bercusson and Cynthia Estlund, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Globalization; LABOR market; Labor Unions; Regulation; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z